Prognostic value of inflammatory markers NLR, PLR, LMR, dNLR, ANC in melanoma patients treated with immune checkpoint inhibitors: a meta-analysis and systematic review - Ou, Yan; Liang, Shufang; Gao, Qiangqiang; Shang, Yongran; Liang, Junfang; Zhang, Weitao; Liu, Sha (Frontiers in Immunology, 2024)
Background Immune checkpoint inhibitors (ICIs) are an emerging tumor treatment pathway after traditional surgery, chemoradiotherapy, and targeted therapy. They have proven to be effective in a variety of cancers, but may not respond to non-target populations. Inflammatory markers such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), derived neutrophil lymphocyte ratio (dNLR), and neutrophil count (ANC) have been shown to be strongly associated with tumor prognosis, but their prognostic significance remains controversial. We therefore performed a meta-analysis to explore the association between NLR, PLR, LMR, dNLR, ANC and prognostic and clinicopathological factors in melanoma patients treated with ICIs. Methods A comprehensive search was conducted in Pubmed, Embase, Web Of Science and Cochrane databases, and the last search time was July 2024. To estimate the prognostic value of NLR, PLR, LMR, dNLR, ANC for PFS and OS, hazard ratio (HR) and corresponding 95% confidence interval (CI) estimates were used. Results This meta-analysis ultimately included 22 cohort studies involving 3235 melanoma patients. Meta-analysis results showed that high levels of NLR in melanoma patients receiving ICIs were associated with poorer OS and PFS, Merging the HR respectively OS [HR = 2.21, 95% CI (1.62, 3.02), P < 0.001], PFS [HR = 1.80, 95% CI (1.40, 2.30), P < 0.001]; High levels of PLR were associated with poor OS and PFS, and the combined HR was OS[HR=2.15,95%CI(1.66,2.80),P < 0.001] and PFS[HR=1.67,95%CI(1.31,2.12),P < 0.001]. High levels of dNLR were associated with poor OS and PFS, with combined HR being OS[HR=2.34,95%CI(1.96,2.79),P < 0.001] and PFS[HR=2.05,95%CI(1.73,2.42),P < 0.001], respectively. High ANC was associated with poor OS and PFS, and combined HR was OS[HR=1.95,95%CI(1.16,3.27),P < 0.001] and PFS[HR=1.63,95%CI(1.04,2.54),P=0.032], respectively. Increased LMR was associated with prolonged OS and PFS, with combined HR being OS[HR=0.36, 95%CI(0.19,0.70),P < 0.001] and PFS[HR=0.56,95%CI(0.40,0.79),P=0.034], respectively. ConclusionIn melanoma patients treated with ICIs, elevated levels of NLR, PLR, dNLR, and ANC were associated with poorer overall survival OS and PFS.